Google Search

Wednesday, September 22, 2010

Postulates and Theorems of Boolean Algebra

Postulate 2

Postulate 5

Theorem 1

Theorem 2

Theorem 3, involution

Postulate 3, commutative

Theorem 4, associative

Postulate 4, distributive

Theorem 5, DeMorgan

Theorem 6, absorption

x + 0 = x

x + x’ = 1

x + x = x

x + 1 = 1

(x’)’ = x

x + y = y + x

x + (y + z) = (x + y) + z

x (y + z) = xy + xz

(x + y)’ = x’y’

x + xy = x

x . 1 = x

x . x’ = 0

x . x = x

x . 0 = 0

xy =yx

x(yz) = (xy)z

x + yz = (x + y)(x + z)

(xy)’ = x’ + y’

x(x + y) = x

No comments:

Post a Comment